General Interest of Spain - González Hernández, Esther (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
This paper intends to define the concept of the “Spanish general interest” used in art. 155 of the Spanish Constitution. This is typically considered as an example of an “undefined legal concept”, which is analyzed here from different perspectives: terminological, semantical, historical and hermeneutical in order to define its true constitutional meaning.
Keywords: “Spanish general interest”; “undefined legal concept”; art. 155 of the Spanish Constitution